Measures for the prevention and treatment of varroatosis in bees. - Rakhimov Mukhamad Yunusovich (Genius Journals, 2022)
The article provides information on the prevention and treatment of varroatosis, which is often found in bees and causes great economic damage. It is an invasive disease that can be acute or chronic. In the prevention of this disease, it is advisable to ensure zoohygienic environmental conditions and the exchange of effective drugs against the disease.
Keywords: Varroatosis; mite; pyrethroid; honeycomb